Social comparison in the workplace: Evidence from a field experiment - Alain Cohn; Ernst Fehr; Benedikt Herrmann; Frédéric Schneider (University of Zurich, Department of Economics, 2011)
We conducted a randomized field experiment to examine how workers respond to wage cuts, and whether their response depends on the wages paid to coworkers. Workers were assigned to teams of two, performed identical individual tasks, and received the same performance-independent hourly wage. Cutting both team members' wages caused a substantial decrease in performance. When only one team member's wage was cut, the performance decrease for the workers who received the cut was more than twice as large as the individual performance decrease when both workers' wages were cut. This finding indicates that social comparison processes among workers affect effort provision because the only difference between the two wage cut conditions is the other team member's wage level. In contrast, workers whose wage was not cut but who witnessed their team member's pay being cut displayed no change in performance relative to the baseline treatment in which both workers' wages remained unchanged, indicating that social comparison exerts asymmetric effects on effort.
Keywords: C93; J33; M53; 330; Compensation; Fairness; Field Experiment; Social Comparison; Vergütungssystem; Arbeitsleistung; Arbeitsgruppe; Soziale Beziehungen; Feldforschung